ANALISA KADAR CHOLINESTERASE DALAM DARAH DAN KELUHAN KESEHATAN PADA PETANI KENTANG KILOMETER XI KOTA SUNGAI PENUH - Marisa Marisa; Nadya Dwi Pratuna (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Pesticides are substances used to kill or control the sharing of pests, said pestisida derived from the word pest which means pest and word cide which means killer, so simply the pesticide is defined as a pest killer that is mites. Cholinitesrase is a liver enzyme used to help determine whether liver function is still good or not. When cholinesterase levels decrease, there is impaired liver function. The type of research used for this research is descriptive, population and sample of research are potato farmer in Kilometer XI Kota Sungai Penuh with 30 samples taken is 10ul capillary blood. And the results obtained are 21 people normal levels (70%), 7 people are mild poisoning(23,%%) and 2 people are poisoned(6,7%).